Mejora del sistema de conducción de aire Comprimido en la empresa Riopaila Castilla S.A. - Guzman Martinez, Andres Felipe; Giraldo Molina, Bernardo Arturo (Universidad Antonio Nariño, 2022)
The improvement of the compressed air conduction system of Riopaila Castilla S.A. is proposed in order to reduce costs due to electricity consumption and maintenance frequency by reducing the replacement of filters, oils and spare parts. The proposed improvements also mitigate the environmental impacts generated by the excessive noise levels produced by the use of compressors. The proposed improvements in the reduction of the use of compressed air generation equipment are aimed at redesigning the current compressed air route.